O trabalho prescrito pela Base Nacional Comum Curricular no eixo de análise linguística sob a visão sociointeracionista - Salatiel, Tarcísio Francisco Oliveira (Universidade do Vale do Rio dos Sinos, 2019)
On this research, we aimed to discuss the prescribed work in the Brazilian federal document Common National Base Curriculum (CNBC), regarding the teaching and practices of linguistics analysis didactic proposal in the middle school, identifying the linguistics-discoursive features which configure the textualization of the prescribed work. We sought contributions on Bronckart (2006,2008,2012) and Machado (2009) to show our theoretical framework based on the Sociodiscoursive Interactionism approach for the notion of prescribed work to the teacher. We also tied it with researches about mother language teaching taken from Mendonça (2006), Antunes (2003;2014), Silva (2015) and Neves (2018) for the concepts of language, interaction and contemporary Portuguese language teaching. Anchored on Mendonça’s reflections, we understand the linguistics analysis section at CNBC document may promote student’s overview about the linguistics facts embeded in the textual production (speaking and writing) as well as for widely understanding of the linguistic system, and create citizens able to produce lots of textual genres with autonomy and adaptation. Based upon the qualitative methodology, we accomplished this research based on the interpretation method which the analytics categories proposed by Machado and Bronckart (2002;2005), spotlighting the prescribed acting, outside determiners, purposes and intentions that entail the actors and agents were embraced in this research corpus. Firstly, we investigated the BNCC document and its linguistics analysis didactic proposal discussion for the Portuguese teaching in order to describe the conceptions prescribed on the document. After that, we interpreted the semantic roles given teachers away, verifying the tools and the roles prescribed to them. This research showed us that, as a national document that focuses on the education development, it requires a comprehensive unfolding that specifies the teacher’s work, enunciating his/her role in the tasks of teaching and learning. To the same extent, it has been needed the engagement to the practice with the linguistics analysis didactic proposal in the Portuguese language classes, stressing language teaching leaned on the interaction, getting students analysts on their own language and not bounded users in the social practices.
Keywords: Base Nacional Comum Curricular; Ensino de Língua Portuguesa; Análise Linguística; Interacionismo Sociodiscursivo; Trabalho Prescrito; Common National Base Curriculum (CNBC); Portuguese Language Teaching; Linguistics Analysis; Sociodiscoursive Interactionism; Prescribed Work; ACCNPQ::Lingüística, Letras e Artes::Lingüística